Copy number variation in selected NK related-genes of acute leukaemia patients at diagnosis and complete remission - Mohd Ashraf Muhamad Asri. (2018)
Introduction: Gene copy number variations (CNV) are structural variations defined by large scale amplifications or deletions of one or more sections of DNA. Acute lymphoblastic leukaemia (ALL) is the malignant transformation of immature B and Tlymphoblast in the bone marrow. Natural Killer (NK) cells exert cytolytic activity against tumour cells but this protective arm may be suppressed in cancer patients. The killing activity of NK cells is controlled by different groups of receptors that exhibit activating and inhibitory functions. Objective: Here, we want to compare gene amplification of selected NK-related genes in paired samples of acute leukaemia patients by performing DNA extraction and Real-time PCR. Methodology: Paired acute leukaemia samples - at diagnosis and complete remission are archived samples collected from Haematology Unit, PPUKM. DNeasy Blood & Tissue Kit from QIAGEN was used to extract DNA from samples. Result: Extraction performed on leukaemia cell lines achieved concentrations up to 44.4 ng/µl. Five pairs of leukaemia samples were obtained. DNA concentrations extracted from cryopreserved leukaemia samples ranged from 13.6 µg/µl to 16.5 ng/µ. DNA quality based on 260/280 were between 1.88- 2.43, showing slightly higher than expected values. However, gel electrophoresis of these samples showed nondegraded bands of good quality. A comparison of the five samples from complete remission showed variation in expression as much as 3.7 fold-differences (NCR3), 3.3 (KLRC4), 2 (KLDR1) to 1.8 (LAIR2). Leukaemia samples at diagnosis normalised to normal samples revealed fold changes of 0.28-4.96 (NCR3). 0.37 - 2.73 (KLRC4), 0 - 2.39 (KLDR1) and 0.85 - 4.03 (LAIR). Conclusion: Variation in gene copy number were observed in the NK-related genes in normal samples. Generation of leukaemia may further amplify or delete gene copy number. Additional samples for confirmation. Key words: Copy number variation, ALL, NK-related genes, germline, somatic/acquired